A look at school time and the single school day. A review of empirical research (2022)
School time is a structuring element of the school experience that gives meaning. This bibliographic review presents the results of various research studies associated with the categories of school time and the single school day. Initially, the school time category is studied as a structuring element of school organization and its subjectivity. The increase in research on this subject in Latin America is described and the main problems addressed are enunciated. Likewise, the perspective of school time as a determining factor in academic results in relation to educational quality is presented. In addition, there are qualitative studies that investigate the perception of school actors regarding the implementation of the single school day policy. There is a tendency for studies related to the objective of educational quality and the school day; however, there are other perspectives that have been little explored and are gaining importance, such as school time from a pedagogical point of view.